Intervening on Calorie Intake or Eating Timing in Older Adults: Lessons Learned in the Healthy Aging and Late-Life Outcomes Randomized Controlled Pilot Trial - Fanning J; Rejeski WJ; Nicklas BJ; Kritchevsky SB; Miller ME; Houston DK; Walkup MP; Kennedy K; Stowe CL; Ford S; Yow D (Clinical Interventions in Aging)
Jason Fanning,1 W Jack Rejeski,1 Barbara J Nicklas,2 Stephen B Kritchevsky,2 Michael E Miller,3 Denise K Houston,2 Michael P Walkup,4 Kimberly Kennedy,2 Cynthia L Stowe,4 Sherri Ford,1 Dixie Yow2 On behalf of the HALLO-P Investigators1Department of Health and Exercise Science, Wake Forest University, Winston-Salem, NC, USA; 2Department of Internal Medicine, Wake Forest University School of Medicine, Winston-Salem, NC, USA; 3Department of Public Health Sciences, Wake Forest University School of Medicine, Winston-Salem, NC, USA; 4Department of Biostatistical Sciences, Wake Forest University School of Medicine, Winston-Salem, NC, USACorrespondence: Jason Fanning, Department of Health and Exercise Science, Wake Forest University, 1834 Wake Forest Road, Winston-Salem, NC, USA, 27103, Email fanninjt@wfu.eduPurpose: The Healthy Aging and Late Life Outcomes Pilot (HALLO-P) trial was designed to pilot in-person and remotely delivered caloric restriction (CR and RCR respectively) and time restricted eating (TRE) in preparation for a long-term multi-site clinical trial. Herein, we describe the development and execution of these behavioral interventions with a focus on lessons learned and post-study questionnaire data.Patients and Methods: Participants were community-dwelling older (60+ yrs) adults with obesity or overweight with an indication for weight loss. Participants were randomized to 9 months of group-based CR, RCR, or TRE supported by self-monitoring technologies [ie, a tablet application paired with an activity monitor (all) and wireless scale (CR and RCR)]. Intervention staff recorded attendance at sessions and noted intervention-related lessons learned as they arose. Upon completion of the study period, participants were asked to complete a series of Likert-type and open-ended questions related to their experiences in the trial.Results: Participants (N = 90; 67.19 ± 4.91 years) attended 84.4% of sessions on average, engaged with study technologies 96.4% of days, and provided daily weights on > 4 days per week across the study (CR and RCR only). Participants reported high satisfaction with the program, with RCR participants being significantly more likely than TRE participants to report being satisfied with their program overall (100% vs 75%, p < 0.01), intending to continue their dietary change post-intervention (97% vs 63%, p < 0.01), and being willing to sustain their dietary approach and engage with study technologies over a 5-year period (88% vs 61%, p < 0.01). Open-ended feedback underscored the value of the group-based structure of the program and remote delivery to reduce travel burden, the need for reduced burden associated with food logging, and the need to identify methods for enhancing perceived value of TRE among older adults.Conclusion: An intervention designed to promote CR, primarily delivered remotely and supported by self-monitoring technology, is both feasible and acceptable to many older adults.Keywords: aging, technology, behavior, obesity, pilot